Type 2 Diabetes Mellitus treatment patterns across Europe: A population-based multi-database study. - Overbeek, J; Heintjes, E; Prieto-Alhambra, D; Blin, P; Lassalle, R; Hall, G; Lapi, F; Bianchini, E; Hammar, N; Bezemer, I; Herings, R (Elsevier, 2017)
Purpose The aim of this study was to determine the similarities and differences of type 2 diabetes mellitus (T2DM) treatment patterns in daily practice in five European countries and whether these reflect differences in the guidelines. Methods Prescriptions for drugs used in diabetes during a 5-year study period were obtained from electronic databases. Patients initiating T2DM treatment during the study period were included. A SAS analysis tool was developed to create episodes of use of drug classes, which resulted in treatment patterns. Findings A total of 253,530 persons initiating T2DM treatment during the study period were included; 52-55% was male and mean age ranged from 62 to 67 years. Metformin was the most common initial treatment in all countries. After initial therapy most patients in the Netherlands, Spain and the UK switched to a combination of metformin + SU. In Italy metformin in combination with SU was outnumbered by ‘other treatment’, mainly because of repaglinide use. In France treatments including DPP-4i were most frequent as second and fourth line treatment. Metformin monotherapy was again most commonly observed as third treatment in all countries. Fourth treatment was a combination of metformin + SU in the Netherlands and Spain, while in the UK and France this was DPP-4i. Implications This study provides a comprehensive overview of T2DM treatment patterns among patients initiating T2DM treatment in five European countries. Differences are present, especially regarding the (uptake of) newer incretin-based treatments, which are usually prescribed as a second and/or third treatment in line with the local guidelines. These differences reflected the differences between the national guidelines of these countries.